2009
DOI: 10.1007/s10704-009-9396-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the loading path on fatigue crack growth under mixed-mode loading

Abstract: International audienceFatigue crack growth testswere performed under various mixed-mode loading paths, on maraging steel. The effective loading paths were computed by finite element simulations, in which asperity-induced crack closure and friction were modelled. Application of fatigue criteria for tension or shear-dominated failure after elastic–plastic computations of stresses and strains, ahead of the crack tip, yielded predictions of the crack paths, assuming that the crack would propagate in the direction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…It should be noted, however, that the shear-mode crack growth was associated with many mode I branches along the crack paths that contributed to deceleration and final bifurcation of mode II cracks. In the maraging steel, Doquet et al 69 observed an immediate transition to mode I branch below ΔK II = 15 MPa m 1/2 . The most frequently observed behaviour was a very short coplanar crack growth that was stopped after 10 μm to create a mode I branch of 70 o , although an immediate branching was observed as well.…”
Section: Mode IImentioning
confidence: 99%
“…It should be noted, however, that the shear-mode crack growth was associated with many mode I branches along the crack paths that contributed to deceleration and final bifurcation of mode II cracks. In the maraging steel, Doquet et al 69 observed an immediate transition to mode I branch below ΔK II = 15 MPa m 1/2 . The most frequently observed behaviour was a very short coplanar crack growth that was stopped after 10 μm to create a mode I branch of 70 o , although an immediate branching was observed as well.…”
Section: Mode IImentioning
confidence: 99%
“…However, due to asperities interlocking and friction, the stress intensity factors computed for a smooth frictionless crack (denoted by K nominal II , K nominal III ) overestimate the effective crack driving force Pinna and Doquet (1999); ; Tschegg and Stanzl (1988); Smith and Smith (1988); Doquet et al (2009);Bertolino and Doquet (2009). Corrections based on a comparison of expected and measured crack face relative sliding displacements had thus to be made.…”
Section: Computation Of Nominal Stress Intensity Factors Along the Crmentioning
confidence: 99%
“…For that purpose, constitutive equations with isotropic and non-linear kinematic hardening fitted to experimental stress-strain curves measured in tension and push-pull for maraging steel and Ti-6Al-4V were used. More details on these equations can be found in Doquet et al (2009);Bertolino and Doquet (2009); .…”
Section: Correction Of Stress Intensity Factors For Crack Face Interamentioning
confidence: 99%
See 1 more Smart Citation
“…At present, experimental FCG investigations are predominantly undertaken for mode I or proportional mixed mode loads. Only a few studies [1][2][3][4][5][6][7][8] focus on non-proportional mixed mode loads. Limited results on A106-93 mild steel [3] reveal that a long and stable shear mode FCG -which is significantly different from the commonly understood open mode FCG -could be produced by non-proportional loads.…”
Section: Introductionmentioning
confidence: 99%